2020
DOI: 10.22207/jpam.14.3.57
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity And Genotoxicity Effect of Ethanolic Leaves Extract of Rosmarinus Officinalis

Abstract: The recent increasing use of artificial antibiotics has prompted an expansion in resistant strains and high site reactions. Medicinal plants have for quite some time been utilized as traditional medicine to treat pathogenic bacteria. In such manner, consistently numerous scientists are sending a range of plant’s secondary compounds to the customer advertise for the treatment of human illnesses. Accordingly, the distinguishing proof of plant spices with antimicrobial impacts can assist with delivering new medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However efficient, methanol poses toxicity concerns, and whenever possible, it should be replaced. Thus, it was shown that aqueous ethanolic solutions used as extraction solvent facilitated polyphenol extraction from herbs [ 18 ]. Water swells the plant matrix, allowing ethanol to penetrate the solid matrices easier, causing a disruption in the bonding between the bioactive compounds and plant matrix, and facilitating a better mass transfer of the compounds [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However efficient, methanol poses toxicity concerns, and whenever possible, it should be replaced. Thus, it was shown that aqueous ethanolic solutions used as extraction solvent facilitated polyphenol extraction from herbs [ 18 ]. Water swells the plant matrix, allowing ethanol to penetrate the solid matrices easier, causing a disruption in the bonding between the bioactive compounds and plant matrix, and facilitating a better mass transfer of the compounds [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Water swells the plant matrix, allowing ethanol to penetrate the solid matrices easier, causing a disruption in the bonding between the bioactive compounds and plant matrix, and facilitating a better mass transfer of the compounds [ 70 ]. Previous results showed that ethanol was a good solvent for extracting bioactive substances from plants, and it was reported to be the best solvent to extract the phenolic compounds from rosemary leaves [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations